Atypical intraductal proliferation detected in prostate needle biopsy is a marker of unsampled intraductal carcinoma and other adverse pathological features: a prospective clinicopathological study of 62 cases with emphasis on pathological outcomes. Issue 3 (2nd July 2019) - Shah, Rajal B; Nguyen, Jane K; Przybycin, Christopher G; Reynolds, Jordan P; Cox, Roni; Myles, Jonathan; Klein, Eric; McKenney, Jesse K
Abstract : Aims: Intraductal proliferations of the prostate with more complexity and/or cytological atypia than high‐grade prostate intra‐epithelial neoplasia (HGPIN), but falling short of intraductal carcinoma (IDC‐P), are described as 'atypical intraductal proliferation' (AIP). When present in needle biopsy (NBX) without IDC‐P, the clinical significance is not known. Methods and results: Sixty‐two NBX cases were diagnosed as AIP over 7 years with estimated incidence of 1%. AIP was characterised by loose cribriform architecture (90%) or non‐cribriform architecture exhibiting significant nuclear atypia that fell short of IDC‐P. Fifty patients had concomitant PCa (20% grade group (GG) 1, 48% GG2, 14% GG3, 8% GG4 and 10% GG 5), and 12 had AIP alone. Of 40 patients who were candidates for no therapy (AIP alone) or active surveillance (AIP with GG1 or GG2 PCa without cribriform pattern 4), 20 had subsequent follow‐up pathology [seven NBXs and 13 radical prostatectomy (RP)]. Of the 12 AIP only patients, six had a subsequent biopsy diagnosis of: benign prostate (two), IDC‐P with PCa (one) and PCa (three). One or more adverse pathological features at subsequent RP were present in 93% of patients with AIP and GG1 or GG2 PCa, defined as: GG ≥ 3 (15%), IDC‐P (77%), cribriform Gleason pattern 4 (69%), pT3a (77%) or pT3b (8%). Conclusions: AIP in NBX may be a marker of unsampled IDC‐P and/or other adverse pathological features in suspected low‐ to intermediate‐risk PCa. AIP should be considered distinct from HGPIN for risk assessment and warrant consideration for further work‐up to detect unsampled high‐risk PCa.